Metaphor in Song Lyrics: Implications for English Language Education - Sugianti Somba; Anggita Citra Paramitha (STKIP Taman Siswa Bima, 2026)
Language serves as a primary medium for expressing ideas, emotions, and experiences, particularly in literary forms such as song lyrics. Metaphor, as a central element of figurative language, plays a crucial role not only in meaning construction but also in supporting language learning. This study aims to identify the types of metaphors and interpret their meanings in the song lyrics of Mandy Moore’s So Real album, as well as to examine their implications for English language education. This research employs a descriptive qualitative method, with data collected through documentation and observation of 13 songs in the album. The findings reveal 28 metaphorical expressions categorized into structural, ontological, and orientational metaphors, with ontological metaphors especially those conceptualizing emotions as containers being the most dominant (35.71%). These results indicate that abstract emotions are systematically represented through concrete domains. Pedagogically, the findings suggest that metaphorical expressions in song lyrics can be effectively integrated into language teaching to enhance learners’ interpretative skills, enrich vocabulary acquisition, and facilitate the understanding of abstract meanings. Furthermore, the use of songs as authentic materials can promote student engagement, critical thinking, and cultural awareness, thereby supporting the development of communicative and cognitive competence in English.